Artemisinin-passivated mixed-cation perovskite films for durable flexible perovskite solar cells with over 21% efficiency. Issue 3 (24th December 2020) - Yang, Longkai; Xiong, Qiu; Li, Yanbo; Gao, Peng; Xu, Ben; Lin, Hong; Li, Xin; Miyasaka, Tsutomu
Abstract : The strong coordination between artemisinin molecules and exposed Pb 2+ ions reduces the perovskite crystal's defects and alleviates Pb clusters, resulting in high-performance flexible perovskite solar cells. Abstract : High power conversion efficiencies (PCEs) surpassing 20% have been achieved on flexible single-junction perovskite solar cells recently. However, improvements of the open-circuit voltage ( V OC ) and fill factor (FF), limited by the nonradiative recombination, and the device durability are needed to boost the practical performance further. Herein, we report the use of artemisinin, an herb extract, to passivate the perovskite grains to improve the V OC and FF of flexible PSCs significantly. The incorporation of artemisinin (0.22 mol%) in the perovskite film reduces the film's trap density and thus the nonradiative recombination effectively. As a result, a best PCE of 21.10% is achieved, comparable with state-of-art values of flexible thin-film solar cells (CIGS, CdTe, etc. ). V OC reaches 1.126 V, corresponding to a V OC loss of 0.437 V. Moreover, the flexible PSCs incorporated with artemisinin always exhibit excellent stabilities under different aging conditions. Strong interactions between the artemisinin molecules and the uncoordinated Pb 2+ ions revealed by theoretical and experimental calculations are responsible for the suppressed formation of new deep-level trap defects, Pb clusters, upon aging.